On the relation between the extended supporting hyperplane algorithm and Kelley's cutting plane algorithm - Felipe Serrano; Robert Schwarz; Ambros Gleixner (Journal of Global Optimization, 2020)
Recently, Kronqvist et al. (J Global Optim 64(2):249–272, 2016) rediscovered the supporting hyperplane algorithm of Veinott (Oper Res 15(1):147–152, 1967) and demonstrated its computational benefits for solving convex mixed integer nonlinear programs. In this paper we derive the algorithm from a geometric point of view. This enables us to show that the supporting hyperplane algorithm is equivalent to Kelley's cutting plane algorithm (J Soc Ind Appl Math 8(4):703–712, 1960) applied to a particular reformulation of the problem. As a result, we extend the applicability of the supporting hyperplane algorithm to convex problems represented by a class of general, not necessarily convex nor differentiable, functions.
Keywords: 510; Convex MINLP; Cutting plane algorithms; Supporting hyperplane algorithm; Nonsmooth Optimization